Let's make the most out of 2023! - Matheus Ballestero; Ricardo Santos de Oliveira (Brazilian Society for Pediatric Neurosurgery, 2023)
Archives of Pediatric Neurosurgery, the official journal of the Brazilian Society of Pediatric Neurosurgery, was established in 2019 and, since then, has had exponential growth! From our first indexing at Google Academics to Latin American and Caribbean Health Sciences Literature (LILACS),  in which we are in the final validation process, much has been built and worked in our journal. Since 2019 we received 117 papers and published 88 articles. In the last year, we had a rejection rate of 19% with 23 days to the first editorial decision. In 2022 we successfully experimented with a new formula, publishing two special issues with 10 papers in each: Craniofacial and Arachnoid cyst.  Besides that, 2022 was a year of international growth. This year we published many articles from China, Egypt, Malaysia, and Mexico! We also evolved in digital technology by inserting the platform in the "Lepidus" administrator and submission by FORMS, which improved the entire system's performance.   On this special occasion, the editorial office would like to extend their greatest appreciation to all editors, and reviewers who have been supportive, and devoted much of their time and effort to nurturing APN. The journal, in particular, would like to thank the authors for submitting their papers to APN. The editorial board thanks you, and the work continues so that we can reach new indexing bases and consolidate as a reference in Word Pediatric neurosurgery.    Let's grow together!!    Happy New year and long life for everyone! Regard to the last 12 months:   -MOST DOWNLOADED PDF ARTICLE: Jucá et al. Prenatal myelomeningocele repair: report of an inaugural case and considerations about the implementation of a new fetal neurosurgery program   -MOST READ ABSTRACT: De Paula et al. Shaken Baby Syndrome: literature review in the last 5 years   -2020-21 Impact factor 0.24